Business owners' features and access to entrepreneurial resources: new insights for accelerator acceptance. Issue 2 (11th September 2021) - Ermilina, Veronika; Farrell, Matthew; Askarzadeh, Fatemeh; Zhang, Jing
Abstract : Purpose: For new ventures, access to entrepreneurship assistantship is the main source of growth and innovativeness. Accelerators, a growing provider of entrepreneurial resources, offer such assistantship. This study aims to identify several factors that might account for a startup's acceptance of accelerator programs. Particularly, this paper examines the impact of a lead founder's country of birth, gender and education on accelerator acceptance. Design/methodology/approach: This study tests the framework with logit regression for a sample of 10, 298 observations for startups in 166 countries over 2016–2018. Findings: This study finds that entrepreneurs from developing countries are less likely to be accepted by accelerators than entrepreneurs from developed economies. Counterintuitively, this study also finds an advantage for female entrepreneurs in accelerator acceptance. Further, the results suggest a positive impact on education. Building on signaling theory, this paper argues and shows that accelerators do not evaluate applicants uniformly. Practical implications: Our comparative study enhances business owners' insight for application to entrepreneurial resources and has meaningful implications for women's entrepreneurship. For policy-making purposes, this study offers more insight on economic development for entrepreneurs' access to global resources. Originality/value: Despite the extant literature demonstrating the benefits of accelerators, determinants of acceptance to these programs, particularly at the individual level, are underexplored. This is the first study that shows the rarely acknowledged link between a lead founder's country of birth, gender and education level on accelerator acceptance. Here, this study extends entrepreneurship literature and shows some sources of variation in access to international accelerator programs.